1987
DOI: 10.1016/0266-7681(87)90064-7
|View full text |Cite
|
Sign up to set email alerts
|

Cold sensitivity after replantation in relation to arterial circulation and vasoregulation

Abstract: Cold intolerance is a common problem after injuries to the hand. To elucidate the mechanism of this cold sensitivity, eight patients with successful replantations of amputations of the thumb or index finger were studied one and half years later. In six patients the Doppler signal from the anastomosed arteries was normal and in two patients signs of mild stenosis were found. All patients had normal or slightly reduced basal finger systolic pressure in the replanted finger. Six had signs of marked vasospasm. Alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…and sympathetic nerve damage. 13,14 In the studies conducted to analyze donor site morbidity of the radial flap, the prevalence of such symptoms varies greatly (from 0 to 38%), [3][4][5]7,[15][16][17] and in no publication has an association between these symptoms and any kind of vascular impairment to the hand demonstrated. In fact, retrospective studies comparing the donor hand to the contralateral "healthy" hand using Doppler ultrasonographic evaluation and thermography techniques 15,18,19 failed to verify any vascular morbidity, as did the only published prospective study we have been able to find to date concerning donor site complications.…”
Section: Discussionmentioning
confidence: 99%
“…26 Lesions in the innervation of the fingers commonly result in cold intolerance due to a disturbance in vasoregulation. 27 There is also evidence that diabetic patients with peripheral neuropathy have such enhanced sensitivity to vasoconstrictors. 28 Although this is a lower motor neuron lesion, sympathetic fibers are affected, and it may be that the autonomic control of vasomotor tone is altered in hemiplegic patients via a lesion in the sympathetic system.…”
Section: Discussionmentioning
confidence: 99%